Training on the use of online payment tools for MSMEs in Tambaan Village, Pasuruan City - Cahyono, Krido Eko; Subagio, Dyajeng Woro; Nurrahma, Aisyah Asri; Ghifary, Muhammad Tahajjudi (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The use of E-Wallets as a payment for several merchants such as ShopeePay and others is very helpful as an effective and efficient payment transaction tool that is also capable of integrating with software that uses the InterActive QRIS Open API Platform. Method: The Program using a socialisation method regarding the benefits of using QRIS, as many MSME actors are still unaware of information on online payment usage. Practical Applications: The activity were directly practised by Tambaan Village MSME actors in using the QRIS application for payment transactions. Thus, the objective of this community service activity is to educate SME operators in Tambaan Village, Pasuruan to enable them to compete and transform in the digital era. Conclusion: MSME actors have been able to understand the importance and benefits of using the Shopee Pay application as a digital payment tool using QRIS. MSME actors are able to apply and manage their Shopee Pay business accounts for transactions and as other payment tools to develop their businesses.